Does financial performance moderate Islamic Corporate Governance and Islamic Social Reporting? - Muawanah Candra Kasih; Veni Soraya Dewi (Jurnal Ilmiah Ekonomi Islam, 2021)
The Effect of Islamic Corporate Governance on Islamic Social Reporting with Financial Performance as a Mediation Variables The sustainable development of Islamic Banking is implemented through Islamic Social Reporting which is a Corporate Social Responsibility towards Allah SWT and society. Disclosure of Islamic Social Reporting can be caused by one of the factors namely Islamic Corporate Governance. This study aims to empirically examine the effect of Islamic Corporate Social Reporting on Islamic Social Reporting with Financial Performance as a mediating variable. The higher the Islamic Corporate Governance will increase the financial performance of Islamic Banking so that it affects the disclosure of Islamic Social Reporting. The sample used in this study was manufacturing sector companies listed on the Financial Fervices Authority from 2014 to 2019. The number of samples in this study were 14 Islamic Banking, out of 8 companies. Determination of the sample is obtained by using purposive sampling. Hypothesis testing is done by path analysis, sobel test, and t statistical test. The results of this study indicate that Islamic Corporate Governance has positive effect on Islamic Social Reporting, Islamic Corporate Governance has a positive effect on Financial Performance, Financial Performance has a negative effect on Islamic Social Reporting and Financial Performance can not mediate the effect of Islamic Corporate Governance on Islamic Social Reporting.